Effect of albumin mediated clustering on the magnetic behavior of MnFe2O4 nanoparticles: experimental and theoretical modeling study. (11th October 2019) - Vasilakaki, Marianna; Ntallis, Nikolaos; Bellusci, Mariangela; Varsano, Francesca; Mathieu, Roland; Fiorani, Dino; Peddis, Davide; Trohidou, Kalliopi N
Abstract: Over the last two decades, iron oxide based nanoparticles ferrofluids have attracted significant attention for a wide range of applications. For the successful use of these materials in biotechnology and energy, surface coating and specific functionalization is critical to achieve high dispersibility and colloidal stability of the nanoparticles in the ferrofluids. In view of this, the magnetic behavior of clusters of ultra-small MnFe2 O4 nanoparticles covered by bovine serum albumin, which is known as a highly biocompatible and environmentally friendly surfactant, is investigated by magnetization measurements, and numerical simulations at an atomic and mesoscopic scale. The coating process with albumin produces a change in the structure, actual size and shape distribution of clusters of exchange coupled particles, giving rise to a distribution of blocking temperatures. The coated system exhibits a superspin glass (SSG) behavior with the SSG freezing temperatures similar to the uncoated ones, providing evidence that the strength of the dipolar interactions is not affected by the presence of the albumin. The DFT calculations show that the albumin coating reduces the surface anisotropy and the saturation magnetization in the nanoparticles leading to lower values of the coercive field in agreement with the experimental findings. Our results clearly demonstrate that the albumin coated clusters of MnFe2 O4 particles are ideal systems for energy and biomedical applications since colloidal and thermal stability as well as biosafety is obtained through the albumin coating.